A thyroid hormone regulated asymmetric responsive centre is correlated with eye migration during flatfish metamorphosis - Campinho, Marco António (2018)
Flatfish metamorphosis is a unique post-embryonic developmental event in which thyroid hormones (THs) drive the development of symmetric pelagic larva into asymmetric benthic juveniles. One of the eyes migrates to join the other eye on the opposite side of the head. Developmental mechanisms at the basis of the acquisition of flatfish anatomical asymmetry remain an open question. Here we demonstrate that an TH responsive asymmetric centre, determined by deiodinase 2 expression, ventrally juxtaposed to the migrating eye in sole (Solea senegalensis) correlates with asymmetric cranial ossification that in turn drives eye migration. Besides skin pigmentation that is asymmetric between dorsal and ventral sides, only the most anterior head region delimited by the eyes becomes asymmetric whereas the remainder of the head and organs therein stay symmetric. Sub-ocular ossification is common to all flatfish analysed to date, so we propose that this newly discovered mechanism is universal and is associated with eye migration in all flatfish.